Identification of red flags for IgG4-related disease: an international European Reference Network for Rare Connective Tissue Diseases framework - Della-Torre, Emanuel; Talarico, Rosaria; Ballarin, Jose; Bozzalla-Cassione, Emanuele; Cardamone, Chiara; Cigolini, Cosimo; Ferro, Francesco; Fonseca, Tomas; Fragoulis, George E.; Galetti, Ilaria; Gerosa, Maria; Hernández-Rodríguez, José; et al. (The Lancet Rheumatology, 2024)
IgG4-related disease is a rare fibroinflammatory condition. Prompt recognition is fundamental to initiate treatment and to prevent organ damage. Diagnostic and classification criteria are primarily intended for use by clinicians with established expertise in IgG4-related disease. Absence of disease awareness among primary care physicians and specialists without expertise in IgG4-related disease remains the main cause of diagnostic delay. We aimed to identify red flags that might increase the suspicion of IgG4-related disease in primary and secondary care settings. A task force of experts in IgG4-related disease from the European Reference Network for Rare Connective Tissue Diseases (ERN-ReCONNET), patient representatives, and primary care physicians derived potential red flags for IgG4-related disease through a systematic literature search and a level of agreement exercise. Five red flags reached 100% agreement among experts: swelling in one or more organ system; pancreatic and biliary tree involvement; increased serum IgG4; IgG4+ plasma cell tissue infiltration; and obliterative phlebitis. Red flags for IgG4-related disease are intended for use in primary and secondary care to improve referral to centres of expertise and prompt early diagnosis.
CRIS-Team Scopus Importer:2024-11-29